2020
DOI: 10.14202/vetworld.2020.642-648
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 coadministration with diclofenac augmented impaired renal function in broiler chickens (Gallus gallus domesticus)

Abstract: Aim: This study aimed to investigate the effects of coenzyme Q10 (COQ10) and diclofenac coadministration on the hepatorenal function in broiler chickens (Gallus gallus domesticus). Materials and Methods: Birds (21 days old) were divided into six groups of eight birds each. The 1st group was the control, the 2nd group was treated orally with COQ10 (30 mg/kg b.wt), the 3rd and 4th groups were treated intraperitoneally with diclofenac sodium at doses 1 and 2 mg/kg b.wt, respectively, and the 5th and 6th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
3
9
0
Order By: Relevance
“…Experiments were conducted when the ages of the chicks were between 7-9 days. This is a suitable experimental animal (chick) model used previously in pharmacological and toxicological studies (8)(9)(10)(11). The Alpha lipoic acid (Lipoic-Forte by AMS®), formalin, and their suppliers were as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments were conducted when the ages of the chicks were between 7-9 days. This is a suitable experimental animal (chick) model used previously in pharmacological and toxicological studies (8)(9)(10)(11). The Alpha lipoic acid (Lipoic-Forte by AMS®), formalin, and their suppliers were as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Albadrany et al. [ 51 ] demonstrated that CoQ10 could not alleviate diclofenac-induced renal injury, but worsened the impaired renal function in a broiler chicken model. Obviously, this study exhibits a quite opposite trend of the roles of CoQ10 in AKI.…”
Section: Protective Properties Of Coq10 In Aki Reported In Experiment...mentioning
confidence: 99%
“…Obviously, this study exhibits a quite opposite trend of the roles of CoQ10 in AKI. It was suggested that COQ10 co-administered with diclofenac might cause a synergistic detrimental effect on renal tissue [ 51 ]. Moreover, it was speculated that COQ10 might inhibit prostaglandin synthesis in the kidney, similar to the biological effects of NSAIDs [ 51 ].…”
Section: Protective Properties Of Coq10 In Aki Reported In Experiment...mentioning
confidence: 99%
See 1 more Smart Citation
“…Diclofenac sodium is a Non-Steroidal Anti-Inflammatory Drug (NSAID), with an average relative inhibition cyclooxygenase 1 and 2 (1). Diclofenac has serious pathological effects such as stomach ulceration, GIT bleeding, liver toxicity, kidney papillary necrosis as well as kidney failure on uses for long periods (2). Recently, use of natural compounds, including those extracted from vegetables, fruits, and herbs, as powerful preventive or therapeutic agents has become a promising approach for inflammation-associated disease chemoprevention (3).…”
Section: Introductionmentioning
confidence: 99%